2009
DOI: 10.4315/0362-028x-72.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Swabs as a Tool in Norovirus Outbreak Investigation, Including Outbreaks on Cruise Ships

Abstract: In this study, we investigated whether environmental swabs can be used to demonstrate the presence of norovirus in outbreak settings. First, a procedure was set up based on viral RNA extraction using guanidium isothiocyanate buffer and binding of nucleic acids to silica. Subsequently, environmental swabs were taken at 23 Dutch restaurants and four cruise ships involved in outbreaks of gastroenteritis. Outbreaks were selected based on clinical symptoms consistent with viral gastroenteritis and time between cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…Food testing was reported in five studies (Morillo et al 2012;Verhoef et al 2008a, b;Boxman et al 2009;Koo et al 1996) for a total of 11 outbreaks (data not shown). Environmental swabs were collected only in the outbreaks described by Boxman et al 2009;Koopmans et al 2006;Takkinen 2006;Verhoef et al 2008a, b (data not shown). Real time-polymerase chain reactions (RT-PCRs) were performed in 56 out of 70 vessels involved, and in 50 of them, the genotype of the NoV was detected.…”
Section: Study Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Food testing was reported in five studies (Morillo et al 2012;Verhoef et al 2008a, b;Boxman et al 2009;Koo et al 1996) for a total of 11 outbreaks (data not shown). Environmental swabs were collected only in the outbreaks described by Boxman et al 2009;Koopmans et al 2006;Takkinen 2006;Verhoef et al 2008a, b (data not shown). Real time-polymerase chain reactions (RT-PCRs) were performed in 56 out of 70 vessels involved, and in 50 of them, the genotype of the NoV was detected.…”
Section: Study Resultsmentioning
confidence: 98%
“…Thirteen of these were subsequently excluded because they did not meet the inclusion criteria: five because they were reports of outbreaks on military ships, and eight because data about the location and the characteristics of the outbreak were not available. Twenty-two articles (Morillo et al 2012;Wikswo et al 2011;Vivancos et al 2010;Xerry et al 2009;Boxman et al 2009;Xerry et al 2008;Chimonas et al 2008;Verhoef et al 2008a, b;Takkinen 2006;Koopmans et al 2006;Ferson and Ressler 2005;Isakbaeva et al 2005;Widdowson et al 2004;Gallimore et al 2003;CDC 2002;Minooee and Rickman 1999;McEvoy et al 1996;Koo et al 1996;Herwaldt et al 1994;Khan et al 1994) met the inclusion criteria and were thus included in our review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The significance of such contamination is strongly indicated in reports in which NoV RNA was detected in environmental samples from hospitals (13), cruise ships (14,15), restaurants (16), and houseboats (17) during recurring or ongoing outbreaks. The high viral load in vomitus and feces (7), low infectious dose (18), and short-term immunity (19) that typify NoV gastroenteritis increase the risk of prolonged outbreaks and environmental spread in semiclosed units, in which strains of NoV genotype II.4 (GII.4) or GII.3 tend to dominate (20).…”
mentioning
confidence: 99%